The Correlation of Vocabulary Mastery and Sentence Structure with Students' Writing Ability - Indah Wulan Dari; Andri Wicaksono; Febriyanti Febriyanti (IJLHE: International Journal of Language, Humanities, and Education, 2021)
This study aims to describe the relationship between vocabulary mastery and sentence structure with the ability to write descriptions of the eighth grade students of SMPN 02 Waway Karya, East Lampung. The author uses the correlational method, meaning that data are collected after all the events in question have taken place. The techniques used in collecting research data are questionnaires, tests, and observations. Based on the results of the study, it can be concluded that, (1) there is a positive and significant correlation between sentence structure and the ability to write descriptions, indicated by a correlation coefficient of 0.766 and a coefficient of determination (R2) of 0.587 or 58.7%, (2) there is a positive and significant correlation between vocabulary mastery and the ability to write descriptions as indicated by a correlation coefficient of 0.662 and a coefficient of determination (R2) of 0.438 or 43.8%, (3) there is a positive and significant relationship between vocabulary mastery and sentence structure and ability of writing a description shown by the correlation coefficient of 0.804 and the coefficient of determination (R2) of 0.646 or 64.6%.